Pengaruh Model Project Based Learning (Pjbl) Terhadap Hasil Belajar Siswa Kelas V Pada Subtema 2 Manusia Dan Lingkungan Di SD Negeri 106857 Ampera - Lidia Samosir; Rio Parsaoran Napitupulu; Canni Loren Sianturi (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research was motivated by the low science learning outcomes of students and the lack of optimal use of learning models, especially in thematic learning. This research aims to determine the effect of the Project Based Learning (PjBL) model on the Learning Outcomes of Class V Students in Theme 1 Animal and Human Movement Organs Subtheme 2 Humans and the Learning Environment 1 and 2 Science Subjects at SD Negeri 106857 Ampera T.A 2023/2024. This research used a pre-experiment with a One Group Pretest-Posttest research design. The population used in this research was all class V of SD Negeri 106857 Ampera, totaling 23 people. The sample used in the research was 23 people. The instruments in this research were documentation and a test of 30 multiple choice questions. The data analysis techniques used are normality test, homogeneity test, N-Gain test and continued with hypothesis testing, namely the t-test. The results of this study show t_count= 25.930 and t_table= 1.717. From these data it can be seen that t_count>t_table, namely 25,930 > 1,717. This means that H_a is accepted, so it can be concluded that there is a significant influence from the use of Project Based Learning (PjBL) on the Learning Outcomes of Class V Students in Theme 1 Animal and Human Movement Organs Subtheme 2 Humans and the Learning Environment 1 and 2 Science Subjects at State Elementary School 106857 Ampera TA 2023/2024.